Enhancing Project Management and Monitoring with Precedence Diagram and Earned Value Method: A Case Study in Construction - Rachmatullah, Sholeh; Said, Badar; Ramadhani, Nilam; Alvionita, Vina (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2024)
An increasing number of projects has created challenges in effectively planning, organizing, and maintaining projects. Project planning becomes a crucial aspect of project management, particularly for monitoring progress and efficiently allocating resources. This study aims to implement the precedence diagram and earned value methods to enhance project management and monitoring. The predence diagram method is used to estimate project completion time, while the earned value method tracks time and budget according to project progress. In this case study, project management activities at CV. Firman Syah are observed. The development process starts with data collection and requirements analysis (functional and non-functional), followed by system architecture design using use case diagrams and Data Flow Diagram (DFD). The database is implemented using MySQL, and the application runs on an Apache web server. Vue.js is used for front-end development, while Lumen is employed for back-end development. The results of Black Box testing indicate that the application is capable of predicting project completion time and associated costs, as well as managing project data.